2018
DOI: 10.11604/pamj.2018.30.65.12975
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and opinions regarding contraception by women of reproductive age in North-West Nigeria

Abstract: IntroductionNorth-west Nigeria is a traditionally high fertility setting. Increasing attention is being channeled into scaling up the various interventions that can reduce high fertility, including enhancing contraceptive uptake among women of reproductive age. However, in order to improve demand for contraception, understanding the level of awareness, knowledge and perception of WRA to contraceptive use is essential. This study examines the level of knowledge and perception of WRA to contraceptive use.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 13 publications
6
20
2
Order By: Relevance
“…Over the years, Nigeria has emerged as one of the countries with the fastest-growing population globally due to the low utilization of contraceptives [ 1 ]. It is estimated that Nigeria’s population exceeds 170 million, and more than 400,000 Nigerian women’s lives are lost to childbirth and associated intricacies from unintended pregnancies every year [ 2 , 3 ]. Research indicates that in countries with high fertility and fecundity rate, such as Nigeria, the promotion of modern contraceptive use prevents approximately 32% and 10% of maternal and child mortality, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, Nigeria has emerged as one of the countries with the fastest-growing population globally due to the low utilization of contraceptives [ 1 ]. It is estimated that Nigeria’s population exceeds 170 million, and more than 400,000 Nigerian women’s lives are lost to childbirth and associated intricacies from unintended pregnancies every year [ 2 , 3 ]. Research indicates that in countries with high fertility and fecundity rate, such as Nigeria, the promotion of modern contraceptive use prevents approximately 32% and 10% of maternal and child mortality, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, Nigeria has become one of the fastest growing population in the world due to low contraceptive use [1]. The estimated population is over 170 million while more than 40,000 women in Nigeria die annually from childbirth and related complications from unplanned pregnancies [2,3]. Globally, family planning is the major approach to population growth control and enhance the economic dividends of the country.…”
Section: Introductionmentioning
confidence: 99%
“…These views and ideas reflect individuals' knowledge, opinions, ideas and views. Notably, mass media and social interaction channels contribute to shaping people's views and ideas about family planning [2,11,13,14]. There has been different assertion suggesting that ideational changes in the way people think as a key factor in fertility decline, changing moral values and decision making.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 55.7% of Saudi women agreed that using contraceptive methods can cause health problems. At last the previously mentioned one (Adefalu et al, 2018).They reported that 69.2% of the Nigerian women agreed that using contraceptives can cause health problems. According to the HBM, if no benefits regarding contraceptive uptake are perceived by women, no behavioural change can take place.…”
Section: Overall Health Beliefs Among Contraceptive Usersmentioning
confidence: 99%
“…They revealed that 47% of Ghanaian women agreed that contraceptives prevent unwanted pregnancies. Fifthly, (Adefalu et al, 2018)who had studied awareness and opinions regarding contraception by women of reproductive age in North-West Nigeria. They reported that 63.4% of the Nigerian women agree that contraceptives used to prevent unwanted pregnancy.…”
Section: Overall Health Beliefs Among Contraceptive Usersmentioning
confidence: 99%